2002
DOI: 10.1093/emboj/21.5.966
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt antagonist Dickkopf-1 is regulated by Bmp signaling and c-Jun and modulates programmed cell death

Abstract: Dickkopf-1 (Dkk-1) has been shown to be a potent inhibitor of Wnt/b-catenin signaling in a variety of assays and organisms. In this study, we show that expression of Dkk-1 overlaps signi®cantly with the sites of programmed cell death in normal as well as mutant vertebrate limb development, and identify several of its upstream regulators, one of which is Bmp-4. Interestingly, Bmp-4 only activates Dkk-1 when it concomitantly induces apoptosis. Moreover, Dkk-1 is heavily up-regulated by UV irradiation and several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
162
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 60 publications
13
162
1
1
Order By: Relevance
“…Hence, induction of Dkk1 may be involved in an apoptosis pathway. This is supported by the observation that Dkk1 is a transcriptional target of p53 and is proapoptotic in limb development (Grotewold and Ru¨ther, 2002), in mesothelioma (Lee et al, 2004), as well as in human glioma cells, where it is induced by DNA damage (Shou et al, 2002).…”
Section: Other Roles Of Dkk1mentioning
confidence: 76%
See 2 more Smart Citations
“…Hence, induction of Dkk1 may be involved in an apoptosis pathway. This is supported by the observation that Dkk1 is a transcriptional target of p53 and is proapoptotic in limb development (Grotewold and Ru¨ther, 2002), in mesothelioma (Lee et al, 2004), as well as in human glioma cells, where it is induced by DNA damage (Shou et al, 2002).…”
Section: Other Roles Of Dkk1mentioning
confidence: 76%
“…An expansion of the AER is observed in both Dkk1 null and hypomorphic Dkk1 d/d mutants, suggesting a genetic interaction with Wnt3 (Mukhopadhyay et al, 2001;Adamska et al, 2004;MacDonald et al, 2004). In the control of the AER, Wnt3 lies upstream of BMP ligands (Barrow et al, 2003) and Dkk1 interacts with BMPs in this context, as they can mutually induce each others expression (Mukhopadhyay et al, 2001;Grotewold and Ru¨ther, 2002).…”
Section: Dkk1 and Limb Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…Hydrogen peroxide, in turn, has been shown to induce Dkk1 expression in MEFs. 12,13 However, thalidomide potentiated DEMinduced Dkk1 expression ( Figure 5A). Importantly, thalidomide-induced apoptosis in DEM-pretreated MEFs was reduced by PBN or MnTBAP as well as by Noggin, Dkk1 blocking antibodies (RDkk1), bpV(pic) or BIO ( Figure 5B,C).…”
Section: Impairment Of the Antioxidant Defense Sensitizesmentioning
confidence: 95%
“…It has been shown that anterior limb mesenchyme is the place for prominent cell death at E11.5 (Grotewold and Ruther, 2002a;our personal data). This finding may be Dickkopf-dependent, as Dkk1 is a BMP target gene (Mukhopadhyay et al, 2001;Grotewold and Ruther, 2002b). At this stage, the Xt/Xt homozygote limb displays an anterior overgrowth that will lead to polydactyly, suggesting that in the absence of Gli3R, cell death is abolished.…”
Section: Downstream Shh: Life and Death In The Limb Fieldmentioning
confidence: 97%